Central serotoninergic system mediates Neuromedin S (NMS) induced hypophagia in layer-type chicken - Najafi, Ehsan; Mahdavi, Kimia; Zendehdel, Morteza; Khodadadi, Mina (Journal of Poultry Sciences and Avian Diseases, 2023)
According to previous studies, the serotonergic system plays a remarkable role in regulating meal intake, however, its role in the mediation of feeding caused by neuromodulin S (NMS) has not been investigated in birds. In the present research, 5 trials were considered in order to determine the links between these systems. In treatment 1, chickens received intracerebroventricular (ICV) infusion of NMS (0.25, 0.5, and 1 nmol). NMS (1 nmol), SB242084 (1.5 μg), a 5-HT2C receptor antagonist, and NMS + SB242084 were injected in the treatment 2. In subsequent treatments, instead of SB242084, 8-OH-DPAT (agonist of 5-HT1A receptor, 15.25 nmol), PCPA (serotonin synthesis inhibitor, 1.25 μg), and Fluoxetine (serotonin reuptake inhibitor, 10 μg) were applied. Then, total food consumption was recorded for 120 minutes. Based on observations, NMS dose-dependently attenuated meal intake (P<0.05). Hypophagia was diminished with NMS + SB242084 administration (P<0.05). ICV infusion of NMU + 8-OH-DPAT had no significant effect on the hypophagia (P≥0.05). The NMS-induced decreasing feed intake was attenuated with co-infusion of NMS+ PCPA (P< 0.05). Also, hypophagia was strengthened by NMS+ Fluoxetine co-infusion (P< 0.05). According to the results, the NMS-induced hypophagia is possibly mediated via 5-HT2c receptors in layer-type chickens.